From Root to Stem: Optimizing Produce Utilization and Reducing Waste through Sustainable Cooking Practices (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: In modern society, food waste is a pressing issue contributing to environmental degradation and resource  depletion. “From Root to Stem” proposes a solution by advocating for sustainable cooking practices that maximize the  use of every part of produce. Objectives: The objectives of this study were twofold. Firstly, to assess the existing levels  of awareness and implementation of root-to-stem cooking practices among hospitality students. Secondly, to identify the  obstacles hindering widespread adoption of root-to-stem cooking and to pinpoint the factors that facilitate its uptake.  Additionally, the study aimed to propose effective strategies for promoting the incorporation of root-to-stem cooking  practices in both domestic and commercial environments. Methodology: To accomplish these goals, a quantitative  research approach, specifically employing a descriptive research design, was utilized. Data collection involved the use  of an online questionnaire distributed via Google Forms among a select group of hospitality students with expertise in  the kitchen. Convenience sampling was employed to gather data, resulting in a sample size of 328 participants. Data  analysis was conducted using SPSS version 23, based on a mixed questionnaire format. Results: The data reveals that  92.1% of respondents are familiar with root-to-stem cooking. However, only 4.3% always incorporate these techniques,  with 58.6% doing so sometimes. 87.4% have received formal education or training on root-to-stem cooking, and 78.1%  believe it can contribute to reducing food waste. Additionally, 56.3% are moderately likely to explore root-to-stem  cooking further in the future. Conclusion: Root-to-stem cooking offers a sustainable solution to minimize food waste by  utilizing entire plants. Despite obstacles like limited consumer awareness and logistical challenges, collaborative efforts  among stakeholders can drive its adoption. Through education, digital platforms, and policy interventions, root-to-stem  cooking can revolutionize culinary practices and promote a more sustainable food system.
Keywords: sustainable cooking practices; root to stem concept; food waste; food sustainability